Manufacturing-constrained multi-objective optimization of local patch reinforcements for discontinuous fiber reinforced composite parts - Fengler, Benedikt (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
In this work, contributes to the optimization of local continuous fiber reinforcement patches, under consideration of manufacturing constraints. This approach requires specific optimization strategies. Therefore, an multi-objective optimization strategy for the placement of local reinforcement patches, under consideration of manufacturing constraints, has been developed. During the multi objective optimization, structural and process related objectives are considered.